Mechanistic modeling and simulation of a complex low and high loading elution behavior of a polypeptide in cation exchange chromatography. Issue 12 (6th April 2022) - Koch, Jonas; Scheps, Daniel; Gunne, Matthias; Boscheinen, Oliver; Hafner, Mathias; Frech, Christian
Abstract : The mechanistic modeling of preparative liquid chromatography is still a challenging task. Nonideal thermodynamic conditions may require activity coefficients for the mechanistic description of preparative chromatography. In this work, a chromatographic cation exchange step with a polypeptide having a complex elution behavior in low and high loading situations is modeled. Model calibration in the linear range of the isotherm is done by applying counterion‐induced linear gradient elution experiments between pH 3.3 and 4.3. Inverse fitting with column loads up to 25 mg/mLCV is performed for parameter estimation in the nonlinear range. The polypeptide elution peak shows an anti‐Langmuirian behavior with fronting under low loading conditions and a switch to a Langmuirian behavior with increasing load. This unusual elution behavior could be described with an extended version of the sigmoidal Self‐Association isotherm including two activity coefficients for the polypeptide and counterion in solution. The activity coefficient of the solute polypeptide shows a strong influence on the model parameters and is crucial in the linear and nonlinear range of the isotherm. The modeling procedure results in a unique and robust model parameter set that is sufficient to describe the complex elution behavior and allows modeling over the full isotherm range.